Is There Full or Proportional Somatosensory Recovery in the Upper Limb After Stroke? Investigating Behavioral Outcome and Neural Correlates. (August 2018) - Boccuni, Leonardo; Meyer, Sarah; Kessner, Simon S.; De Bruyn, Nele; Essers, Bea; Cheng, Bastian; Thomalla, Götz; Peeters, André; Sunaert, Stefan; Duprez, Thierry; Marinelli, Lucio; Trompetto, Carlo; et al.
Background. Proportional motor recovery in the upper limb has been investigated, indicating about 70% of the potential for recovery of motor impairment within the first months poststroke. Objective. To investigate whether the proportional recovery rule is applicable for upper-limb somatosensory impairment and to study underlying neural correlates of impairment and outcome at 6 months. Methods. A total of 32 patients were evaluated at 4 to 7 days and 6 months using the Erasmus MC modification of the revised Nottingham Sensory Assessment (NSA) for impairment of (1) somatosensory perception (exteroception) and (2) passive somatosensory processing (sharp/blunt discrimination and proprioception); (3) active somatosensory processing was evaluated using the stereognosis component of the NSA. Magnetic resonance imaging scans were obtained within 1 week poststroke, from which lesion load (LL) was calculated for key somatosensory tracts. Results . Somatosensory perception fully recovered within 6 months. Passive and active somatosensory processing showed proportional recovery of 86% (95% CI = 79%-93%) and 69% (95% CI = 49%-89%), respectively. Patients with somatosensory impairment at 4 to 7 days showed significantly greater thalamocortical and insulo-opercular tracts (TCT and IOT) LL ( P < .05) in comparison to patients without impairment. Sensorimotor tract disruption at 4 to 7 days did not provide significant contribution above somatosensory processing score at 4 to 7 days when predicting somatosensory processing outcome at 6 months. Conclusions. Our sample of stroke patients assessed early showed full somatosensory perception but proportional passive and active somatosensory processing recovery. Disruption of both the TCT and IOT early after stroke appears to be a factor associated with somatosensory impairment but not outcome.